PENINGKATAN KUALITAS LAYANAN, KINERJA KARYAWAN DAN KEPUASAN KONSUMEN MELALUI PELATIHAN SOFTSKILL (PROGRAM PENGABDIAN KEPADA MASYARAKAT PADA BKS LPD UBUD) - I WAYAN SUARTINA; I.G. ARYANA MAHAYASA; TJOK ISTRI TUTY I; IDA I DEWA AYU YAYATI WILYADEWI (JURNAL SEWAKA BHAKTI, 2019)
The LPD (Village Credit Institution) as an institution that runs the financial functions of traditional and Pakraman villages, is required to have a good performance base, so that it can increase the level of trust and satisfaction of the Pakraman village community as the main consumers of the LPD. One of the efforts to improve LPD performance is by improving the skills and capabilities of human resources that are owned in serving their customers in accordance with the concept of Tri Hita Karana. This community service activity is carried out on LPDs under the management of the BKS LPD Ubud targeting the employees and managers of the LPD. Community service aims to provide an understanding of how basic techniques (soft skills) perform excellent service to customers to improve customer satisfaction, and how to deal with customer complaints and make the complaint a tool to improve service. The method of community service activities is by providing practical skills training provided directly to employees and managers of LPDs under the BKS Ubud, which includes delivery/concept presentations, group discussions, role play/games and case studies. This activity was conducted for one day and was attended by 45 employees and managers of LPDs in the BKS LPD Ubud. The benefits obtained from the results of this training activity are increasing motivation, ability and basic skills of employees facing consumers in accordance with SOP (Standard Operating Procedure) of policy makers and LPD managers, especially those who are members of the Ubud BKS in maintaining quality service to LPD consumers.